Do red cell alloantibodies continue to challenge breast fed babies?. Issue 4 (21st February 2020) - Rasalam, Jess E.; Kumar, Snehil; Amalraj, Pushpanathan; Bal, Harshjeet S.; Mathai, John; Kumar, Manish; Sridhar, Santhanam; Daniel, Dolly
Abstract: Background: Newborns have limited specific immune capability at birth, owing to delayed and constrained development of adaptive immunity. To supplement this period the mother passively transfers antibodies to the child either transplacentally or through breast milk. When maternal alloimmunisation occurs through foreign or fetal red cell surface antigens, stimulating the production of immunoglobulin G (IgG) antibodies, these IgG antibodies can cross the placenta and cause haemolytic disease of the fetus and the newborn. Objective: We present two case reports of a neonate and an infant in whom IgG red cell alloantibodies were transferred through maternal breast milk. Methods: Maternal serum, baby's serum and expressed breast milk samples were tested for the presence of red cell alloantibodies using gel card. Antibody screening, antibody identifications and titres alongside monospecific direct antiglobulin test, IgG subtypes were performed using the standard methods. Results: In the first case, a 6‐month‐old child was incidentally found to have positive antibody screen. Anti‐KELL1 was identified, which was also present in maternal serum and breast milk. The second neonate was evaluated for haemolysis and was found to have anti‐D. Anti‐D was also detected in the maternal serum and breast milk. Both babies did not have any sensitising events. The first baby was asymptomatic, but the second baby had ongoing haemolysis until 1 month. Conclusion: We report that maternal anti‐KELL1 and anti‐D antibodies were present in breast milk and were capable of being transferred to a feeding child. Our case report also raises interesting and unanswered immunologic fundamentals that should be considered in neonates with unexplained anaemia or delayed and persistent haemolysis.